1997
DOI: 10.1074/jbc.272.45.28342
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Mammalian and PlantS-Adenosylmethionine Decarboxylase Proenzymes

Abstract: S-Adenosylmethionine decarboxylase (AdoMetDC) is a pyruvoyl enzyme, and the pyruvate is formed in an intramolecular reaction that cleaves a proenzyme precursor and converts a serine residue into pyruvate. The wild type potato AdoMetDC proenzyme processed much faster than the human proenzyme and did not require putrescine for an optimal rate of processing despite the presence of three acidic residues (equivalent to ) is not present in the potato sequence. The site of potato AdoMetDC proenzyme processing was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(131 citation statements)
references
References 37 publications
5
125
0
1
Order By: Relevance
“…The amino acid residues corresponding to those of the human proenzyme previously shown to be required for catalytic activity (Glu8, Glu11, Ser68, Cys82, Ser229, and His243 in the human sequence), and putrescine stimulation of processing and activity (Glu11, Glu15, Arg76, Lys80, Asp174, Glu178, and Glu256) are identical or similar in the N. crassa AdoMetDC (Fig. 3) (Stanley and Pegg 1991;Stanley et al 1994;Xiong et al 1997Xiong et al , 1999 . The conservation of these residues suggests that proenzyme processing and the catalytic activity of the N. crassa enzyme might be stimulated by putrescine.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The amino acid residues corresponding to those of the human proenzyme previously shown to be required for catalytic activity (Glu8, Glu11, Ser68, Cys82, Ser229, and His243 in the human sequence), and putrescine stimulation of processing and activity (Glu11, Glu15, Arg76, Lys80, Asp174, Glu178, and Glu256) are identical or similar in the N. crassa AdoMetDC (Fig. 3) (Stanley and Pegg 1991;Stanley et al 1994;Xiong et al 1997Xiong et al , 1999 . The conservation of these residues suggests that proenzyme processing and the catalytic activity of the N. crassa enzyme might be stimulated by putrescine.…”
Section: Resultsmentioning
confidence: 99%
“…By 30 min after inhibition of translation, virtually all the proenzyme was processed, with a corresponding increase in the intensity of the band representing the mature a subunit. This is rapid compared to the human AdoMetDC: only 15% of this precursor is converted to the mature enzyme after 30 min in the absence of putrescine (Xiong et al 1997). A previous study (Xiong et al 1997) found that the TNT reticulocyte lysate, used in these experiments, contained insucient putrescine (<1 nM) to stimulate the processing of human AdoMetDC.…”
Section: Stimulation Of N Crassa Adometdc Activity By Putrescinementioning
confidence: 99%
See 2 more Smart Citations
“…All of the known sequences, except that from Escherichia coli, show a significant degree of similarity with about 50 fully conserved residues in the core region of 300 amino acids. This includes the sequences (KTCGTT) that contain an essential active site lysine and cysteine residues (Stanley and Pegg, 1991;Stanley et al, 1994;Xiong et al, 1997). In spite of rather extensive studies on the functionally important residues of AdoMetDC, almost all of the studies were confined to the enzyme active site (Stanley and Pegg, 1991;Stanley et al, 1994;Xiong et al, 1999), except the essential Cys 83 residue in the active site.…”
Section: Introductionmentioning
confidence: 99%